Cultural realities of being abstract ideas within everyday lives - Chaudhary, Nandita; Anandalakshmy, S.; Valsiner, Jaan (London Routledge/Taylor & Francis Group, 2014)
"Cultural Realities of Being offers a dialogue between academic activity and everyday lives by providing an interface between several perspectives on human conduct. Very often, academic pursuits are arcane and obscure for ordinary people, this book will attempt to disentangle these dialogues, lifting everyday discourse and providing a forum for advancing discussion and dialogue. Nandita Chaudhary, S. Anandalakshmy and Jaan Valsiner bring together contributors from the field of cultural psychology to consider how people living within social groups, regardless of how liberal, are guided by collective reality and interconnected with life circumstances. The book discusses experiences and events in the lives of people of Indian cultures covering topics including family, food, pilgrimages, social dynamics and truth, in order to expand the material on human phenomena under the broad frame of cultural psychology. The book builds upon rich cultural traditions present in India, and precisely because of this focus, the book has much larger implications and relevance to the field and aims to orient the academic reader from around the world to viewing India and Indian society as a valuable area for research. Divided into three sections, the book covers: Social presentation in culture, Representing relations, Children and youth in culture. This book includes commentaries from expert academics from outside of India, providing a bridge between academic reality and cultural discourse and throwing fresh light on the everyday events presented in the text. Cultural Realities of Being will be essential reading for those studying Cross Cultural Psychology as well as those interested in social representation and identity"-- Provided by publisher.
Introspections on culture / S. Anandalakshmy -- Feasting and fasting in Hindu India / Devdutt Pattanaik -- Commentary / Alan Roland -- Negotiations with patriarch : gender and childhood in India / Shraddha Kapoor -- Parental reconstructions about the care and development of young children / Mila Tuli -- Cultural situatedness of cognitive development and its assessment / Nandita Chaudhary -- Commentary / Ana Cecilia Bastos -- " I have a family, therefore I am" : children's understanding of self and others / Pooja Bhargava -- Children's understanding of multiple layers of truth / Punya Pillai -- Challenging tradition and negotiating modernity : the lives of contemporary Indian youth / Sujata Sriram -- Commentary / Meike Watzlawik -- General conclusion.
Includes bibliographical references and index.
Keywords: Social psychology -- India; Psychoanalysis and culture -- India; Group Identity -- India; Child psychology -- India; Children -- Social conditions -- India; PSYCHOLOGY / Social Psychology; India -- Social conditions -- 1947-.